Armenia - Programmatic Public Expenditure Review : Raising Efficiency in Infrastructure Services - World Bank (Washington, DC : World Bank, 2022)
This module draws upon the work of the local consultants together with the Avag report on irrigation and a study on the specific problems in rural infrastructure. It aims to given a broad overview of infrastructure problems, the outlook given public policy objectives, and a suggested public policy framework and proposes medium term policy, structural, governance and regulatory improvements in the sector. In Armenia considerable progress has been made in bringing infrastructure services up to economically efficient levels. But major challenges remain concerning service quality, sustainability and adequacy of development to meet demand. The government faces three challenging issues in respect of infrastructure: the desirability of policy settings consistent with sustained high rates of growth; improving the stewardship of state infrastructure assets; and making effective use of future investments, particularly those arising from donor contributions such as the millennium challenge corporation along with funds from customers. Consistent with implementation of the Government's growth and poverty alleviation strategy and related policy settings supportive of the continuation of rapid economic growth including high rates of private investment. The report estimates that addressing basic minimum infrastructure needs will require about US$300 million of investment.